The Characterization of Cardiac Explants Reveals Unique Fibrosis Patterns and a Predominance of CD8+ T Cell Subpopulations in Patients with Chronic Chagas Cardiomyopathy - Martha Lucía Díaz; Fredy A. Delgado; Ruth A Martínez; Mayra Alejandra Jaimes; Luis Eduardo Echeverría; Sergio Alejandro Gómez-Ochoa; Julio César Mantilla-Hernández; Clara Isabel González (Pathogens, 2022)
Aim: The present study aimed to characterize the histopathological findings and the phenotype of inflammatory cells in the myocardial tissue of patients with end-stage heart failure (ESHF) secondary to CCC in comparison with ESHF secondary to non-Chagas cardiomyopathies (NCC). Methods: A total of 32 explanted hearts were collected from transplanted patients between 2014 and 2017. Of these, 21 were classified as CCC and 11 as other NCC. A macroscopic analysis followed by a microscopic analysis were performed. Finally, the phenotypes of the inflammatory infiltrates were characterized using flow cytometry. Results: Microscopic analysis revealed more extensive fibrotic involvement in patients with CCC, with more frequent foci of fibrosis, collagen deposits, and degeneration of myocardial fibers, in addition to identifying foci of inflammatory infiltrate of greater magnitude. Finally, cell phenotyping identified more memory T cells, mainly CD8+CD45RO+ T cells, and fewer transitioning T cells (CD45RA+/CD45RO+) in patients with CCC compared with the NCC group. Conclusions: CCC represents a unique form of myocardial involvement characterized by abundant inflammatory infiltrates, severe interstitial fibrosis, extensive collagen deposits, and marked cardiomyocyte degeneration. The structural myocardial changes observed in late-stage Chagas cardiomyopathy appear to be closely related to the presence of cardiac fibrosis and the colocalization of collagen fibers and inflammatory cells, a finding that serves as a basis for the generation of new hypotheses aimed at better understanding the role of inflammation and fibrogenesis in the progression of CCC. Finally, the predominance of memory T cells in CCC compared with NCC hearts highlights the critical role of the parasite-specific lymphocytic response in the course of the infection.